Propuesta de reestructuración de la red logística y de transporte para el proceso de aprovisionamiento de la empresa Caravela Coffee SAS (2023)
The design of a supply logistics network is a way of managing the supply chain, in such a way that all activities are integrated, seeking to improve the relationships in the chain, with the aim of achieving competitive advantages in an increasingly competitively logistically speaking.